2021
DOI: 10.1186/s12916-021-02108-z
|View full text |Cite|
|
Sign up to set email alerts
|

Socioeconomic position and prognosis in premenopausal breast cancer: a population-based cohort study in Denmark

Abstract: Background To investigate how socioeconomic position (SEP) influences the effectiveness of cancer-directed treatment in premenopausal breast cancer patients in terms of breast cancer recurrence and mortality. Methods We conducted a cohort study nested in the ProBeCaRe (Predictors of Breast Cancer Recurrence) cohort (n = 5959). We identified all premenopausal women aged 18–55 years diagnosed with non-metastatic breast cancer and prescribed docetaxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Despite the aforementioned conclusion being given in the analysis conducted within this study, an inspection of the education-related graph shown in the study ( Fig. 1 ) reveals that there is no statistically significant disparity in the mortality risk among patients with varying levels of education [ 39 ]. Based on this, it seems that additional studies are important to identify the effect of education level on recurrence, survival and mortality of relapsed patients.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the aforementioned conclusion being given in the analysis conducted within this study, an inspection of the education-related graph shown in the study ( Fig. 1 ) reveals that there is no statistically significant disparity in the mortality risk among patients with varying levels of education [ 39 ]. Based on this, it seems that additional studies are important to identify the effect of education level on recurrence, survival and mortality of relapsed patients.…”
Section: Discussionmentioning
confidence: 98%
“…influence treatment compliance, particularly among women experiencing side effects (36). Previous studies also showed that uninsured premenopausal patients are more likely to forgo effective treatment for financial reasons and to opt out of follow-up programs, causing recurrences to remain underdetected (36,37). According to SEER data, the rate of BCT between 2000 and 2006 in the United States was 55-60% (38).…”
Section: Discussionmentioning
confidence: 99%
“…Unmarried women are reportedly more likely to develop advanced-stage breast cancer, as having a spouse may represent a factor supporting the early detection of malignancy ( 34 , 35 ). Social support from a partner might also influence treatment compliance, particularly among women experiencing side effects ( 36 ). Previous studies also showed that uninsured premenopausal patients are more likely to forgo effective treatment for financial reasons and to opt out of follow-up programs, causing recurrences to remain under-detected ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in breast cancer diagnosis and increasingly effective treatments (including the introduction of taxanes) have enlarged the pool of breast cancer survivors [ 3 5 ]. Still, mortality measured up to 15 years after premenopausal breast cancer ranges from 11 to 14% in high-income countries [ 2 , 6 ]. Reasons for variation in individual treatment effectiveness are likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%